Pengaruh Harga, Iklan Media Sosial dan Lokasi terhadap Minat Beli Konsumen pada Café Dots Karawang - Kirana Narama Fadillah; Dadan Ahmad Fadili (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine and explain the level of consumer buying interest in Cafe Dots Karawang based on price, social media advertising and location. This research was conducted through a statistical technique approach using IBM SPSS 25, data collection using random sampling technique on 325 respondents with research subjects being consumers of Cafe Dots Karawang. The data analysis technique used is the scale range analysis technique and multiple regression analysis. The magnitude of the partial effect of price on consumer buying interest is 0.200 or 20%. The magnitude of the partial effect of Social Media Ads on Consumer Purchase Interest is 0.380 or 38%. The partial influence of location on consumer buying interest is 0.169 or 16.9%. Then the magnitude of the simultaneous influence of Price, Social Media Advertising and Location has a positive and significant effect on Consumer Purchase Interest Dots Karawang with a contribution of 0.269 or 26.9% and the remaining 73.1% other contributions are influenced by variables not examined.